Factors that Motivate Persons with Physical Disabilities to Engage in Physical Activity - Norgilas, Robertas; Masiliauskas, Darius (Jaunųjų mokslininkų darbai, 2020)
Factors that motivate persons with physical disabilities to engage in physical activity have been analysed in this paper. The analyzed topic is in line with the priorities to increase the level of physical activity among different social groups, especially taking into account that the current level of physical activity is insufficient. With reference to this, a search for decisions, aimed at increasing physical activity of persons with reduced mobility, is relevant. This can be achieved only when factors, that motivate such persons to engage in physical activity have been identified. The study revealed that motivation to engage in physical activity draws on three dimensions - intrinsic, extrinsic motivation and amotivation. Results of empirical study confirm that persons with reduced mobility are motivated to engage in physical activity by both intrinsic and extrinsic motivation.